(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Methionine, an essential amino acid, plays an essential role in the central nervous system CNS development. It serves as a crucial intermediate in the methylation, trans-sulfuration and amino- phosphorylation pathways, necessary for the synthesis of nucleic acids, phospholipids, hormones, neurotransmitters, antioxidants, polyamines, catecholamines and other biogenic amines. The effect of methionine on learning and memory in mice was investigated using Morris water maze (MWM), Elevated plus maze(EPM) and Y maze (YM). Animals were administered with distilled water (control), methionine (1,700mg/kg); folate (3mg/kg) or methionine (1700mg/kg) plus folate (3mg/kg) for 14 days. Escape latency and time spent in target quadrants; transfer latency and percentage spontaneous alternations were measured in the MWM, EPM and YM respectively. The animals were anaesthetized with inhalational chloroform and their brains subsequently harvested, homogenized and assayed for acetylcholinesterase24 hours after the experiment. Folate significantly(p<0.05) increased transfer latency (53.33 ± 12.62) as compared to control (20.1 ± 5.01) and reduced spontaneous alternations significantly (25.0 ± 8.9) when compared to control (44.33 ± 3.07). When folate was combined with methionine there was also a significant increase in transfer latency (43.0 ± 14.39) when compared with control (20.1 ± 5.01). Folate-methionine combination also significantly (p<0.05) reduced spontaneous alternations (20.4 ± 8.4) as compared to the control (44.33 ± 3.07) much more than folate alone. Acetylcholinesterase activities in all groups were not statistically significant. It can be concluded that acute methionine administration has some benefits in memory enhancement. However, a short course folate supplementation impairslearning and working memory especially when combined with methionine which may be as a result of sudden overwhelming of the methylation cycle, leading to homocysteinemia which is pro-dementia.